Educational Consequences of a Sibling's Disability: Evidence from Type 1 Diabetes - Tine Louise Mundbjerg Eriksen; Amanda Gaulke; Niels Skipper; Jannet Svensson; Peter Rønø Thingholm (Institute of Labor Economics (IZA), 2023)
While there is a growing literature on family health spillovers, questions remain about how sibling disability status impacts educational outcomes. As disability is not randomly assigned this is an empirical challenge. In this paper we use Danish administrative data and variation in the onset of type 1 diabetes to compare education outcomes of focal children with a disabled sibling to outcomes of focal children without a disabled sibling (matched on date of birth of the focal child, sibling spacing and family size). We find that having a disabled sibling significantly decreases 9th grade exit exam GPAs, while having no impact on on-time completion of 9th grade. However, educational trajectories are impacted, as we find significant decreases in high school enrollment and significant increases in vocational school enrollment by age 18. Our results indicate that sibling disability status can generate economically meaningful inequality in educational outcomes.
Keywords: I1; I2; J1; 330; sibling spillovers; health; diabetes; educational performance; SES